Smelting Conditions and Smelting Products: Experimental Insights into the Development of Iron Bloomery Furnaces - Yvette A. Marks; N. Groat; L. O. Lortie; M. Hughes; H. F. Thompson; C. J. Woodland; T. MS Adams; T. Thorpe; B. Tang; R. Kenyon; B. Langhorne; J. Fraser-Darling (EXARC Journal)
The material record for bloomery furnaces in Iron Age and Roman Britain is fragmentary and, because of this paucity of evidence, the reconstruction of the ceramic structures used in iron production is difficult. Experiments have nevertheless been carried out to explore the working parameters and efficiency of iron smelting in bowl furnaces (small structures with little structure above ground level, interior measuring about 30 cm in height) (Craddock, 1995; Girbal, 2013) and shaft furnaces (height c.1m) (Smith, 2013; Crew, 2013; Doonan and Dungworth, 2013; Tylecote and Merkel, 1985; Tylecote and Wynne, 1958). These experiments aimed to clarify which furnace is more efficient for iron smelting and therefore what method was most likely used in Iron Age and Roman Britain. It is theorised that iron smelting furnaces developed from bowl structures to shaft structures over time, as smelters sought furnaces which could reach higher temperatures and create more reducing atmospheres (Dungworth 2013; Tylecote and Merkel, 1985; Tylecote and Wynne, 1958). These experiments suggest that the shaft furnace was used as it could meet these requirements. This study looks at the working conditions of a shaft furnace at an intermediary height - between that of a bowl furnace and of a shaft furnace - in order to understand its working parameters and to consequently better understand the progression from a bowl to a 1m high shaft structure.